Characteristics and Classification of some Upper Slope Soils in Savanna Ecosystems of South Western Nigeria - OJO-ATERE , J. O.; OLADIMEJI, M. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Some upper slope soils of the savanna ecosystems of south-western Nigeria were studied with a view to broaden their data base and pave the way for a better classification of the soils.             The three profiles used were obtained from Shaki, Igbeti and Baba-Ode in the northern part of Oyo State. The soils were subjected to physical, chemical, mineralogical and micro-morphological analyses. Generally, it was observed that the morphological and chemical characteristics of the soils studied have been affected considerably by the interaction of climate, parent material, relief, vegetation, time and biological factors. The physical, chemical and mineralogical data do not show any well-defined sequence in the profiles. These analytical data indicate that the surface horizons may be developed in transported material, while the subsurface horizons may be derived from the underlying rock. These indicate the completely of the profiles and also confirm the non-uniformity of the parent materials. Clay mineralogy indicates that Kaolinite is dominant in the soils, with considerable amounts of smectite-and mica. Cutans were associated with both Inceptisols and Alfisols in the soils studied. Thus, cutahs may not be a good diagnostic feature for argillic horizons in south western Nigeria.